Fire modelling framework for investigating tall building fire: A case study of the Plasco Building - Aatif Ali Khan; Mustesin Ali Khan; Ramakanth Veera Venkata Domada; Xinyan Huang; Asif Usmani; Saeed Bakhtiyari; Masoud Jamali Ashtiani; Sadegh Garivani; Ali Akbar Aghakouchak (Case Studies in Thermal Engineering, 2023)
Fire can damage structures severely and even cause the building collapse. Structural and fire engineers must carry out a comprehensive forensic investigation of major structural failures in the same rigorous and meticulous manner the airline industry investigates air crashes. The forensic assessment should identify the cause, fire spread scenario, fire behaviour patterns from its growth to decay, de-compartmentation, the performance of fire protection systems, and firefighting management. Using the available tools and data, the current paper proposes a methodology to reconstruct the fire for the forensic assessment of tall buildings. This is done by first organising observed data into a coherent timeline and presenting the actual fire spread obtained from the visual evidence. The total fire spread within the building is estimated based on fire dynamics principles and observed fire scenes that can be verified with a calibrated CFD model. The collapse of the Plasco Building is assessed by employing the proposed framework. The rise in construction of the tall buildings increases the risk of the occupants’ safety from the fire induced structural failure or collapse. The framework presented in this paper can guide engineers to improve the building resilience designs and reduce the fire accidents related risks.